Analisis Faktor-Faktor Yang Mempengaruhi Pola Pengelolaan Keuangan Mahasiswa Ekonomi - Khusnul Ashar; Fariza Hanum Azriana (Universitas Sains dan Teknologi Komputer, 2024)
Good financial management is an important aspect of student life, especially for those studying economics. Economics students are expected to have a deep understanding of personal financial management and long-term financial planning. However, not all students have the same ability to manage finances. This research aims to analyze the factors that influence the financial management patterns of students at the Faculty of Economics and Business, Brawijaya University. This research uses a quantitative research method with a cross-sectional survey design, namely, data was collected from 50 students through a structured questionnaire. The research results from this method show that the factors that influence the financial management of economics students are monthly income, knowledge about finance, attitudes toward financial management, experience in financial management, social support, and personal financial needs and goals. Suggestions that can be given to university is to provide guidance to their students include holding regular training on financial management, inviting financial experts to give seminars or guest lectures, and holding student financial counseling.